2015
DOI: 10.1115/1.4031040
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Gravity and Turbidity Currents: Computational Approaches and Challenges

Abstract: In this review article, we discuss recent progress with regard to modeling gravity-driven, high Reynolds number currents, with the emphasis on depth-resolving, high-resolution simulations. The initial sections describe new developments in the conceptual modeling of such currents for the purpose of identifying the Froude number–current height rela-tionship, in the spirit of the pioneering work by von Karman and Benjamin. A brief intro-duction to depth-averaged approaches follows, including box models and shallo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
79
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 81 publications
(80 citation statements)
references
References 165 publications
(227 reference statements)
0
79
0
1
Order By: Relevance
“…As opposed to simulations within closed or periodic geometries, such as the lock-exchange configuration, open flows are somewhat more challenging because attention has to be paid to minimising any numerical contamination of the flow by upstream propagation of the outflow boundary conditions. For a broader discussion of the computational challenges associated with modeling gravity currents, we refer the reader to Meiburg et al (2015).…”
Section: Introductionmentioning
confidence: 99%
“…As opposed to simulations within closed or periodic geometries, such as the lock-exchange configuration, open flows are somewhat more challenging because attention has to be paid to minimising any numerical contamination of the flow by upstream propagation of the outflow boundary conditions. For a broader discussion of the computational challenges associated with modeling gravity currents, we refer the reader to Meiburg et al (2015).…”
Section: Introductionmentioning
confidence: 99%
“…Piomelli [31] argued that the cost of a calculation scales like the Reynolds number to the power 2.4 for LES. The computational cost of LES model is about 4-100-times higher than that required by the RANS model [43,44].…”
Section: Model Descriptionmentioning
confidence: 97%
“…More recent reviews on the numerical modeling of turbidity current may be found in. [23][24][25] Numerical model study…”
Section: Field and Physical Model Studiesmentioning
confidence: 99%